Operational tolerance after pediatric composite liver‐pancreas‐intestine transplantation following severe graft‐versus‐host disease. (14th June 2021) - Osborn, Julie; Nathan, Jaimie D.; Tiao, Gregory; Alonso, Maria; Kocoshis, Samuel
Abstract: Background: While operational tolerance has been previously described in isolated intestinal transplant, reports of this phenomenon in combined liver‐intestine transplant are lacking. Case Description: We detail a unique case of a patient who received a composite allograft including liver, pancreas, and small bowel due to short gut syndrome secondary to gastroschisis complicated by volvulus. The indication for transplantation was permanent dependence on total parenteral nutrition, end‐stage liver disease, recurrent sepsis, and persistent stomal variceal hemorrhage. The patient developed severe graft‐versus‐host disease with grade 3 skin involvement, ophthalmic, and pulmonary involvement with 53% donor T‐cell chimerism. She required aggressive therapy including high‐dose methylprednisolone, rituximab, cyclophosphamide, and alemtuzumab. Due to infection concerns following depletion of her lymphocytes, immunosuppression was discontinued with close surveillance of her allograft. Nearly 10 years later, the patient has continued off all immunosuppression without evidence of rejection or graft dysfunction and demonstrates immunocompetence with normal functional immune assays and development of appropriate live vaccination titers. Conclusion: This report of operational tolerance following pediatric composite liver‐pancreas‐intestine transplantation provides evidence that the complex immunologic balance in intestinal transplantation may on rare occasions favor immunosuppression reduction or even discontinuation. Future trials of immunosuppression minimization in this population may be warranted.